Preprocedural Colchicine in Patients With Acute ST-elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention: A Randomized Controlled Trial (PodCAST-PCI). Issue 4 (October 2022) - Hosseini, Seyed Hossein; Talasaz, Azita H.; Alidoosti, Mohammad; Tajdini, Masih; Van Tassell, Benjamin W.; Etesamifard, Nasrin; Kakavand, Hessam; Jalali, Arash; Aghakouchakzadeh, Maryam; Gheymati, Azin; Sadeghian, Mohammad; Jenab, Yaser
Abstract: Primary percutaneous coronary intervention (PPCI) is the gold standard of treatment in patients with acute ST-elevation myocardial infarction (STEMI). The no-reflow phenomenon (NRP) is a detrimental consequence of STEMI. Colchicine is an anti-inflammatory drug that may help prevent the NRP and improve patient outcomes. In a randomized, double-blind, placebo-controlled clinical trial, 451 patients with acute STEMI who were candidates for PPCI and eligible for enrollment were randomized into the colchicine group (n = 229) and the control group (n = 222). About 321 patients were eligible to participate; 161 patients were assigned to the colchicine group, whereas 160 patients were assigned to the control group. Colchicine was administered 1 mg before PCI and 0.5 mg daily after the procedure until discharge. NRP, measured by angiographic findings including the thrombolysis in myocardial infarction flow grade and the thrombolysis in myocardial infarction myocardial perfusion grade, was reported as the primary outcome. Secondary end points included ST resolution 90 minutes after the procedure, P-selectin, high-sensitivity C-reactive protein, and troponin levels postprocedurally, predischarge ejection fraction, and major adverse cardiac events (MACE) at 1 month and 1 year after PPCI. NRP rates did not show a significant difference between the 2 groups ( P = 0.98). Moreover, the levels of P-selectin, high-sensitivity C-reactive protein, and troponin were not significantly different. MACE and predischarge ejection fraction were also not significantly different between the groups. In patients with STEMI treated by PPCI, colchicine administered before PPCI was not associated with a significant reduction in the NRP and MACE prevention (trial registration: IRCT20120111008698N23).